EVALUATION OF SCHOOL OPERATIONAL ASSISTANCE PROGRAM POLICY - Deding Ishak (Institut Pendidikan Tapanuli Selatan, 2022)
Various problems occur in the BOS funding program in Mamasa District. The purpose of this study was to be able to collect information related to the results of the evaluation of the implementation of the school operational assistance (BOS) program in elementary schools in Mamasa Regency, through observation and evaluation measurements using evaluation criteria such as effectiveness, adequacy, equity, responsiveness, and accuracy. A qualitative method or approach with a case study research design will be used in this study. Data was collected through direct observation in the field, in-depth interviews, and thorough documentation. Informants are determined purposively through the suitability of prospective informants with the required information. Then the data were analyzed through data reduction, data presentation, and concluding.The results of this study provide a conclusion in the form of an evaluation of the program for delivering school operational assistance funds in elementary schools in the Mamasa Regency, showing that this program has been implemented quite well and can be continued. Unfortunately, this program still has shortcomings and weaknesses, so there needs to be a review to improve the success and maximization of the objectives of the BOS fund program itself.